2022
DOI: 10.1101/2022.03.25.22271716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stairway visual contrast enhancement to reduce fall-related events

Abstract: Falls on stairs occur frequently and pose a significant health and financial risk. Laboratory research has found that fall frequency can be reduced through contrast enhancement of the stairs by applying vinyl striping to the first and last steps' faces, and all the steps' top edges. Here we sought to determine if such step contrast enhancement can reduce the probability of fall-related events such as loss of balance, slips, trips, and falls in public university staircases. Cameras were used to capture stair us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Here we sought to evaluate whether an intervention, namely the addition of black stripes to the top, front edge of each step, could counteract the impact of inter-step inconsistencies on the number of observed slips, trips, and falls (fall-related events). As described previously (Harper, 2022), Elliott, Foster, and colleagues have demonstrated that vertical, monochrome striping on the face of the bottom and top steps can increase vertical foot clearance (Elliott et al, 2015;Elliott et al, 2009;Foster et al, 2016;Foster et al, 2015a;Skervin et al, 2021). Adding highcontrast visual strips along the top front edge of all the steps (Cohen & Sloan, 2016;den Brinker et al, 2005;Elliott et al, 2015;Foster et al, 2014a;Thomas et al, 2021;Zietz et al, 2011) could lead to increases in heel clearance.…”
Section: Introductionmentioning
confidence: 86%
“…Here we sought to evaluate whether an intervention, namely the addition of black stripes to the top, front edge of each step, could counteract the impact of inter-step inconsistencies on the number of observed slips, trips, and falls (fall-related events). As described previously (Harper, 2022), Elliott, Foster, and colleagues have demonstrated that vertical, monochrome striping on the face of the bottom and top steps can increase vertical foot clearance (Elliott et al, 2015;Elliott et al, 2009;Foster et al, 2016;Foster et al, 2015a;Skervin et al, 2021). Adding highcontrast visual strips along the top front edge of all the steps (Cohen & Sloan, 2016;den Brinker et al, 2005;Elliott et al, 2015;Foster et al, 2014a;Thomas et al, 2021;Zietz et al, 2011) could lead to increases in heel clearance.…”
Section: Introductionmentioning
confidence: 86%